Perancangan Alat Karakterisasi Dioda dengan ESP32 dan Rangkaian Op-Amp LM358 Berbasis Android - Ari Bawono Putranto; Zaenul Muhlisin; Amatul Lutfiah; Fakhruddin Mangkusasmito; Megarini Hersaputri (Ultima Computing : Jurnal Sistem Komputer, 2021)
This research has succeeded in making a diode forward bias characterization test device using the ADC and the internal DAC of the ESP32 microcontroller. The output voltage of the DAC is added by 2 times the LM358 non-reversing op-amp amplifier circuit. So that the test results of the DAC output voltage can reach a maximum value of 6.3 volts as a source of variable DC power supply for the diode forward bias characteristic test circuit. Diode forward bias characterization testing is carried out through the interface of an Android smartphone with a WiFi network and a forward bias characterization curve is obtained which has a value and shape almost the same as the manual test. Testing the diode forward bias characterization using this application is faster than using manual measurements with a multimeter measuring instrument. Based on tests carried out using the Android smartphone application for 3 times, it was obtained an average time of 30 seconds, while manually using a measuring instrument obtained an average time of 657.7 seconds.